1994
DOI: 10.1007/bf02600025
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of treatment of socially rehabilitated methadone maintenance patients in physicians’ offices (medical maintenance)

Abstract: Carefully selected methadone maintenance patients in medical maintenance have a high retention rate and a low incidence of substance abuse and lost medication. Voluntary withdrawal from methadone maintenance after one or two decades is possible. The authors believe that medical maintenance should be made available to appropriate patients in other localities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 17 publications
2
34
0
1
Order By: Relevance
“…Recent studies have shown that there is a dose-dependent increment in favorable patient outcome with the infusion of rehabilitation medical and psychiatric services . Also, studies of medical maintenance (discussed below) have documented that patients who have responded to methadone maintenance treatment with cessation of illicit opiate use, along with cessation of other illicit drug use, and have succeeded in rehabilitation efforts, may no longer need regular counseling services, but clearly benefit, as do all persons, by access to ongoing medical care (NOVICK and JOSEPH 1991;NOVICK et al 1988aNOVICK et al ,b, 1990NOVICK et al , 1994. These findings have suggested that in the future, to assure medically effective as well as socially and cost effective treatment, there will be a need to define both the severity and various types of codependency, comorbidity, and multiple medical problems at time of entry, and to provide on site or ready access to treatment or management for these problems, as well as a need for diverse social services.…”
Section: B) Treatment Effectiveness and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that there is a dose-dependent increment in favorable patient outcome with the infusion of rehabilitation medical and psychiatric services . Also, studies of medical maintenance (discussed below) have documented that patients who have responded to methadone maintenance treatment with cessation of illicit opiate use, along with cessation of other illicit drug use, and have succeeded in rehabilitation efforts, may no longer need regular counseling services, but clearly benefit, as do all persons, by access to ongoing medical care (NOVICK and JOSEPH 1991;NOVICK et al 1988aNOVICK et al ,b, 1990NOVICK et al , 1994. These findings have suggested that in the future, to assure medically effective as well as socially and cost effective treatment, there will be a need to define both the severity and various types of codependency, comorbidity, and multiple medical problems at time of entry, and to provide on site or ready access to treatment or management for these problems, as well as a need for diverse social services.…”
Section: B) Treatment Effectiveness and Outcomementioning
confidence: 99%
“…Studies have been conducted in at least three cities and are possibly ongoing in other cities to determine the feasibility and effectiveness of medical maintenance treatment for long-term methadone-maintained patients who have had a good record of treatment performance to be treated in a general clinic or "office based" practice. In the New York City studies, under the leadership of Novick, patients who have had at least 5 years of methadone maintenance treatment in a standard clinic, with excellent performance, that is, with cessation of all illicit opiate use and no ongoing polydrug or alcohol abuse, all positive indicators for rehabilitation, met the inclusion criteria (NOVICK et al 1988a(NOVICK et al ,b, 1990(NOVICK et al , 1994NOVICK and JOSEPH 1991). In this medical maintenance study, patients are seen as infrequently as once every 4 weeks or not more often than once a week, in a medical office (not a drug abuse treatment program) at which time they provide a urine speciment for drug monitoring, take one daily dose of methadone under observation, and undergo a conventional medical, and also intense drug use history, physical examination, and when appropriate, other laboratory testing.…”
Section: D) Medical Maintenance Treatment (Office Based Treatment)mentioning
confidence: 99%
“…Despite positive reports evaluating the use of MMM interventions in patients with long-term stable and positive treatment responses (Fiellin et al, 2001;Novick et al, 1994; Salsitz et al, 2000;Schwartz, Brooner, Montoya, Currans, & Hayes., 1999;Senay et al, 1993), adoption of the intervention has been slow. At least two unresolved issues may be hindering the broader adoption of this intervention in community-based treatment settings: The first issue involves the lack of research on effective management strategies for MMM patients who relapse to drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Two published studies have reported successful medical maintenance programs in which stabilized (e.g. no evidence of active drug use for 1 or more years) methadone-maintained patients were transferred from care in narcotic treatment programs to medical maintenance settings (76,77,96). These programs have reported retention rates of 73%-85% for up to 3 years in some patients (77,96).…”
Section: Methadone Maintenance In Physician's Officesmentioning
confidence: 99%